RANCANG BANGUN SISTEM INFORMASI PENGADUAN MASYARAKAT BERBASIS WEB PADA DINAS KOMINFO KABUPATEN LANGKAT - Iqbal Hanafi Ilham; Hanna Willa Dhany; Afif Badawi (CV. Hawari, 2026)
The Department of Communication and Informatics (Kominfo) of Langkat Regency plays an important role in receiving and handling public complaints related to public services. Previously, the complaint process was conducted manually through paper forms, short messages, and face-to-face reporting, which caused several problems such as delays in report delivery, difficulties in tracking complaint histories, and lack of transparency for the public. This study aims to design and develop a web-based Public Complaint Information System to improve report management effectiveness and public service quality. This research applies a software engineering approach using the Waterfall development model consisting of problem identification, data collection, requirement analysis, system design, implementation, testing, and evaluation. The system was developed using PHP, HTML, CSS, and JavaScript programming languages with a MySQL database. The main features include online complaint submission, report management by administrators, complaint status monitoring by the public, and automatic report generation. The results show that the developed system facilitates the public in submitting complaints without visiting the government office directly. In addition, the system assists officers in managing complaint data in a structured manner, accelerates complaint handling processes, and increases transparency in public services. Therefore, the web-based public complaint information system can be an effective solution to support faster, more accurate, and efficient services at the Langkat Regency Kominfo Office.